2006
DOI: 10.1097/01.idc.0000195907.84587.c0
|View full text |Cite
|
Sign up to set email alerts
|

Does Identification of an Extended-Spectrum β-Lactamase-producing Organism by the Microbiology Laboratory Influence Patient Management?

Abstract: Identification of extended-spectrum b-lactamase (ESBL)-producing organisms in clinical specimens was initiated recently by microbiology laboratories. We sought to determine if this practice influences patient management. Retrospective review identified 35 patients with infections caused by ESBL-producing Escherichia coli or Klebsiella species. After receipt of the ESBL report, antimicrobial therapy was changed in 33 patients (94%), and 23 (66%) were placed in isolation. Identification of ESBL producers by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[ 23 24 25 ] Hence, reliable and accurate detection of ESBL in a microbiology laboratory is a must. In a recent study conducted by Gavin et al .,[ 26 ] it was found that the majority of physicians changed therapy after a report of an ESBL-producing pathogen from microbiology laboratory highlighting the importance of ESBL detection. Since no data on ESBL prevalence in our area were available, a study was conducted in our institute to look for prevalence of ESBL among members of the family Enterobacteriaceae and antimicrobial susceptibility pattern of such isolates.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 24 25 ] Hence, reliable and accurate detection of ESBL in a microbiology laboratory is a must. In a recent study conducted by Gavin et al .,[ 26 ] it was found that the majority of physicians changed therapy after a report of an ESBL-producing pathogen from microbiology laboratory highlighting the importance of ESBL detection. Since no data on ESBL prevalence in our area were available, a study was conducted in our institute to look for prevalence of ESBL among members of the family Enterobacteriaceae and antimicrobial susceptibility pattern of such isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratories must critically look for ESBL‐producing pathogens, as indicated by a recent study by Gavin et al. [26], who found that the majority of physicians changed therapy after a report of an ESBL‐producing pathogen from the laboratory; 40% altered the regimen to appropriate monotherapy; and another 23% substituted an active for the initially used inactive antibiotic. After the microbiology report was generated, 54% of the patients were treated with piperacillin–tazobactam, 20% with a carbapenem, and 11% with a fluoroquinolone.…”
Section: Implications For Patient Carementioning
confidence: 99%